Diversification Prospects in Middle East and North Africa (MENA) Equity Markets: A Synthesis and an Update - Olusi, Olasupo; Abdul-Majid, Haikal (2012)
This study investigates the extent to which Eurozone and Middle East and North Africa (MENA) equity markets are integrated, to assess any potential diversification benefits across the two sets of markets. In addition to cointegration analysis, we analyse time-varying conditional correlations, which are then modelled as a smooth transition logistic trend model to permit the determination of the speed at which the two sets of markets are becoming more or less integrated. Optimal portfolios based on a combination of equity assets in both sets of markets are constructed to assess possible gains from diversification. We compare the performances of these portfolios using a variety of performance measures, taking into account the implications of higher moments of return distribution unlike several studies. Whilst our findings do not indicate Eurozone-MENA integration, there is mixed evidence on the correlation trends between the sets of markets. Moreover, the changes in correlations occur at a very slow pace. Overall, our analysis indicates the existence of diversification benefits in MENA equity markets.